Travel Manifestations Ibn Darrage Alkastali's Poetry (Damascus University Journal of arts and humanities sciences, 2021)
This research addresses the emotional aspects of the life of the poet Ibn Darrage Alkastali  to highlight his travel poetry that resonates in most of his poems.The research provides an overview of the life of the poet,   the age he lived in, and the concept of travel and its definition.  It highlights the poet's travels and their causes and stages. The study also discusses how the poet describes his travels and the longing to one's homeland, while toiling for one's family away from one's country. The research provides also an in-depth description of the poet's attempts to describe painful scenes of parting, farewells, the horrors of the journey and the suffering of the children who are left without the head of the family, along with longing for one's homeland.
Keywords: Travel Manifestations Ibn Darrage Alkastali's Poetry